This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
x = 1 ∑ ∞ 6 x 2 + 6 x 3 = 2 1 x = 1 ∑ ∞ x 2 + x 1 = 2 1 x = 1 ∑ ∞ x ( x + 1 ) 1 Using partial fraction decomposition : = 2 1 x = 1 ∑ ∞ x 1 − ( x + 1 ) 1 The series ∑ x = 1 ∞ x 1 − ( x + 1 ) 1 converges (telescopes) to 1 . Multiplied by 2 1 gives us 2 1 Rounding to the nearest ones gives us 1 .